Mamayog the music of Samaon Sulaiman - Bien, Juliet R.; Sulaiman, Samaon 1953-2011; Peralta, Francis Paul B.; Rastrollo, Renato S. (Manila Gawad sa Manlilikha ng Bayan, National Commission for Culture and the Arts, 2011)
Introduction includes historical background on the kutyapi with detailed description of its tuning, structure, and playing technique. Also includes biographical information on kutyapi performer and composer, Samaon Sulaiman. Musical transcriptions of Samaon Sulaiman's kutyapi music.
Keywords: Folk music -- Philippines